Transposed Letter Effect Towards Oral Reading Speed: A Quantitative Study - Zahwa, Ken Putri Choerani; Roistika, Nia (Fakultas Ilmu Budaya, Universitas Brawijaya, 2025)
Transposed Letters Effect (TLE) is a cognitive phenomenon in which readers can recognize words with internal letters swapped, as long as the first and last letters remain in place. This study aims to examine the differences in oral reading speed between normal texts and transposed-letter texts among advanced EFL learners. A quantitative comparative design was employed, involving 15 eighth-semester students from the English Education Department at Universitas Bhinneka PGRI in the academic year 2024/2025. Reading speed data were collected through academic reading tasks and analyzed using the Wilcoxon Signed-Rank Test in JASP software. The result revealed a significant difference (p < 0.001) between reading speeds for normal and transposed texts, with transposed texts read more slowly. However, students showed improvement in reading speed for transposed text after preliminary study, with speeds increasing from 78.53 to 89.87 words per minute. Based on calculations, transposed text was approximately 48.47% slower than normal text in the preliminary study, and still 36.33% slower in the main oral reading test. The findings suggest that while orthographic disruptions significantly reduce oral reading speed, repeated exposure and familiarity can contribute to measurable improvement. This study offers empirical insight into the cognitive constraints of reading fluency and highlights pedagogical implications for developing academic reading skills in EFL contexts.